Substance Abuse among Kashmiri People: Modern Era and Consequences. - Aabid Hussain (AlQalam Journal of Medical and Applied Sciences, 2020)
Substance abuse is when use legal or illegal substances in ways you should not. You might take more than the regular dose of pills or use someone else’s prescription. Drug abuse is defined as taking a drug for reasons other than medical, in an amount, strength frequency and manner that damages the physical or mental functioning. People may abuse drugs to feel good, ease stress or avoid reality. Substance abuse, also known as drug abuse, is use of a drug in amounts or by methods which are harmful to the individual or others. It is a form of substance-related disorder and person is well aware of threat but still consume it. According to a report published in United Nation Drug Control Program (UNDCP) around 70,000 people of Kashmir valley are drug addicts and quite shocking that approximately 31% are women. As per the data available from Youth Development and Rehabilitation Centre Srinagar (previously Known as Drug De-Addiction and Rehabilitation center DDRC) that the youth of Kashmir are particularly involved in drug addiction who fall into the age group between 17-35 years. Besides the mode of drug has completely changed means people are directly landing to hard core drugs like Heroin, Brown-Sugar, Medicinal-opioids, LSD and cocaine which is more alarming. The present paper is theoretical in nature and aims to highlighting the issues and challenges faced by youth of Kashmir in particular.